2015
DOI: 10.1038/ejhg.2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigations of sudden unexpected deaths in infancy using next-generation sequencing of 100 genes associated with cardiac diseases

Abstract: Sudden infant death syndrome (SIDS) is the most frequent manner of post-perinatal death among infants. One of the suggested causes of the syndrome is inherited cardiac diseases, mainly channelopathies, that can trigger arrhythmias and sudden death. The purpose of this study was to investigate cases of sudden unexpected death in infancy (SUDI) for potential causative variants in 100 cardiac-associated genes. We investigated 47 SUDI cases of which 38 had previously been screened for variants in RYR2, KCNQ1, KCNH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 44 publications
2
55
1
Order By: Relevance
“…Our higher percentage may be due to a comprehensive genetic analysis including both genes associated with channelopathies and genes associated with cardiomyopathies, recently associated with arrhythmic pathologies without any structural alteration [52, 53]. In concordance with our results, recent studies performed in post-mortem samples using NGS technology showed percentages of rare variants potentially pathogenic in 30%-40% of samples analyzed [2426, 5458]. …”
Section: Discussionsupporting
confidence: 90%
“…Our higher percentage may be due to a comprehensive genetic analysis including both genes associated with channelopathies and genes associated with cardiomyopathies, recently associated with arrhythmic pathologies without any structural alteration [52, 53]. In concordance with our results, recent studies performed in post-mortem samples using NGS technology showed percentages of rare variants potentially pathogenic in 30%-40% of samples analyzed [2426, 5458]. …”
Section: Discussionsupporting
confidence: 90%
“…We also found EBSEQ to have high analytical reliability of 99% for base substitutions and small deletions and duplication and clinical sensitivity of 75% to 98%. EBSEQ was used in this study primarily to identify mutations in undiagnosed patients, although even when the clinical phenotype is typical of a specific diagnosis, we are studying the type and location and ultimately the consequences of these mutations to increase understanding and predict clinical severity and prognosis . Tenedini and colleagues recently published a similar NGS assay on 10 patients, and there is a report of a commercial laboratory (GeneDx, Gaithersburg, MD, USA) using whole‐exome sequencing to screen for EB .…”
Section: Discussionmentioning
confidence: 99%
“…Target DNA was captured, amplified, and purified based on fragment size. The Haloplex Target Enrichment System for Illumina was used for library preparation. Probes were designed using Agilent's web‐based SureSelect Custom Design portal.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic testing as part of the forensic investigation has proven to be beneficial in, for example, suspected cases of sudden cardiac death [13][14][15]. However, only few studies have used NGS for post-mortem genetic investigations [16][17][18][19][20]. We aimed to investigate the diagnostic outcome for FH by broader genetic screening using NGS in a post-mortem setting in individuals with IHD.…”
mentioning
confidence: 99%
“…The relevant DNA regions were isolated by a capture method using the custom design of the Haloplex Target Enrichment system (Agilent Technologies, CA, USA) with 150-bp read lengths [20]. The design included all coding exons, 25 bp of adjacent introns as well as 5′-and 3′-UTR regions of the eight investigated genes to a total size of 51, 941 bp.…”
mentioning
confidence: 99%